Factors Associated with Severe Bacterial Septic Arthritis at NongKhai Hospital - ติณหภัทร, จินตาหรา (Journal of Health Science of Thailand, 2025)
Septic arthritis is a medical emergency due to its potential to cause disability and significant mortality. Permanent loss of joint function was found in approximately 25.0-50.0% of survivors, and a mortality rate of 3.0-25.0%. The most common cause is bacterial infection. Delayed diagnosis of bacterial septic arthritis and inadequate or delayed treatment can lead to disability and increased mortality rates. This study aimed to determine (1) the factors associated with severe bacterial septic arthritis at NongKhai Hospital, and (2) the incidence, diagnostic approaches, and treatment of patients with bacterial septic arthritis. The present study method was descriptive by collecting retrospective data from 2016-2023. The factors associated with severe bacterial septic arthritis were analyzed by Univariate analysis. Only factors which p<0.20 were further analyzed by multiple logistic regression (p<0.05). Altogether 202 eligible patients were enrolled. It was found that the factors associated with severe bacterial septic arthritis included age >60 years, eGFR <60 mL/min/1.73 m2, albumin <3.0 g/dL, and HCO3 ≤20 mEq/L (p<0.05). Therefore, patients with bacterial septic arthritis should be evaluated for the factors mentioned above and be closely monitored to reduce the risk of disability and death.